2020
DOI: 10.3389/fpls.2020.00921
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization of the C-repeat Binding Factor (CBF) Gene Family Involved in the Response to Abiotic Stresses in Tea Plant (Camellia sinensis)

Abstract: Genome-Wide Characterization of the C-repeat Binding Factor (CBF) Gene Family Involved in the Response to Abiotic Stresses in Tea Plant (Camellia sinensis). Front. Plant Sci. 11:921.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 62 publications
6
37
1
2
Order By: Relevance
“…Previous gene expression studies have reported that most AP2/ERFs are expressed at low levels under normal conditions, but their expression can be induced or repressed at certain growth stages by hormones and stress stimuli (Xie et al, 2019 ). The DREB subfamily may be a key candidate for future exploration of a means to enhance drought and cold tolerance in tea (Ban et al, 2017 ; Parmar et al, 2019 ; Wang et al, 2019 ; Hu et al, 2020 ). It has been classified into six subgroups (A1–A6) (Sakuma et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous gene expression studies have reported that most AP2/ERFs are expressed at low levels under normal conditions, but their expression can be induced or repressed at certain growth stages by hormones and stress stimuli (Xie et al, 2019 ). The DREB subfamily may be a key candidate for future exploration of a means to enhance drought and cold tolerance in tea (Ban et al, 2017 ; Parmar et al, 2019 ; Wang et al, 2019 ; Hu et al, 2020 ). It has been classified into six subgroups (A1–A6) (Sakuma et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many transcription factors and metabolite-related genes have been shown to be involved in both the cold and drought responses of plants. For example, the key cold regulators ICE, CBF , and DHN transcription factors participate in both cold and drought and in other abiotic stresses (Liu et al, 2015 ; Liu S.-C. et al, 2016 ; Yin et al, 2016 ; Ban et al, 2017 ; Hu et al, 2020 ). The genes involved in the ABA-independent responsive pathway and the bZIP -mediated ABA-dependent pathway (Wang et al, 2012 ; Ban et al, 2017 ) also participate in tolerance to cold and drought.…”
Section: Introductionmentioning
confidence: 99%
“…CBF 4 expression is more activated by the exogenous application of ABA in Arabidopsis and grapevine. CBF 1 − 3 expression was also enhanced with the ABA external applications in main part due to the increased activity of CBF promoters in reply to ABA 54,56,57 . The differences in CBF proteins in grapevine re ect the positioning of CBF 4 in the separate phylogenetic groups compared to CBF 1,2, 3 19,58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…The genes involved in the ABA-independent responsive pathway and the bZIP -mediated ABA-dependent pathway participate in tolerance to osmotic stress induced by drought and cold [ 22 ]. In tea plants, 12 major TF-families are believed to be involved in the osmotic stress response viz., AP2/EREBP, bHLH, bZIP, HD-ZIP, HSF (HSP), MYB, NAC, WRKY, zinc-finger protein TFs, SCL, ARR, and SPL [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Many sugar metabolism genes were also induced in response to osmotic stress in tea [ 33 ].…”
Section: Introductionmentioning
confidence: 99%